ISOLASI DAN IDENTIFIKASI MIKROBA SIMBION SPONGE Axinella sp. - Asadatun Abdullah (Institut Pertanian Bogor, 2006)
Sponges are host organisms for various symbiotic microorganisms. Various symbiotic microorganisms have been found in Sponges such as archaea, heterotrophic bacteria, cyanobacteria, green algae, red algae, cryptophytes, dinoflagellates, and diatoms. The objectives of the research were to isolate and identify teh Axinella sp. Sponge-symbiotic microoganisms such asbacteria, micro fungi, and yeast. Sponge-symbiotic microoganisms that have been isolated cosisted of 7 bacteria isolates, 3 micro fungi, and 2 yeast isolates. Result from this research showed that the genus of bacteria was Alteromonas, Bacillus, and 2 yeast isolates have not been to identified.